A simultaneous trajectory generation method for quadcopter intercepting ground mobile vehicle. (6th July 2017) - Zhu, Jiangcheng; Zhu, Jun; Xu, Chao
This article proposes a trajectory generator for quadcopter to intercept moving ground vehicle. For this air–ground interaction problem, we formulate the trajectory generation problem as quadratic dynamic programming in a moving-horizon scheme based on the quadcopter kinematics and observation to ground vehicle. The closed-form solution of quadratic dynamic programming in each iteration enables this algorithm a real-time replanning performance. Thereafter, segmented trajectory rule, inspired from commercial flight landing regular, is implemented to guarantee smoothness in approaching and interception to moving ground target from comparably far origin. Our established algorithm is verified through both simulations and experiments.